Spontaneous coronary artery dissection; a systematic review of physical and psychosocial recovery following discharge from hospital. (2nd July 2022) - Neubeck, L; Mchale, S; Ross, M; Galbraith, M; Hanson, C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Edinburgh Napier University Introduction: Spontaneous coronary artery dissection (SCAD) is increasingly recognised as an important cause of myocardial infarction, particularly among women. SCAD survivors may not know what physical activity is safe and effective and there may be a psychosocial burden of living with a SCAD diagnosis. This review aimed to determine the evidence regarding physical activity, cardiovascular risk factors, or associated factors, and the psychosocial impact of SCAD for SCAD survivors after hospital discharge. Methods: A systematic review completed in accordance with PRISMA guidelines Results: The review included 28 studies. These used a range of methods. None were randomised controlled trials. There were 4167 SCAD participants although some were sourced from the same SCAD registries, so may not be unique. They were mainly female (n=3897 93.5%, range=57.7%-100%), with mean age 48.0±9.8 years at index event. Participants mostly came from the USA, Canada, or the Netherlands. We found very limited evidence for cardiorespiratory fitness improvements following cardiac rehabilitation (CR). Existing CR was not tailored to SCAD specific needs and SCAD survivors lacked guidance about appropriate physical activity. Some participants had high levels of psychosocial distress. SCAD survivors highlighted the need for tailored support that included family members. Many SCAD survivors have traditional risk factors including hypertension, hyperlipidaemia and overweight/obesity. Chest pain following SCAD is common. Conclusions: There is an urgent need to develop physical and psychological recovery programmes for SCAD survivors, and test effectiveness via randomised controlled trials. Psychosocial support is particularly required, given the high burden of psychosocial issues.